Randomised, double-blind, parallel group, placebo-controlled study to evaluate the analgesic efficacy and safety of VVZ-149 injections for postoperative pain following laparoscopic colorectal surgery. Issue 2 (17th February 2017) - Nedeljkovic, Srdjan S; Correll, Darin J; Bao, Xiaodong; Zamor, Natacha; Zeballos, Jose L; Zhang, Yi; Young, Mark J; Ledley, Johanna; Sorace, Jessica; Eng, Kristen; Hamsher, Carlyle P; Maniam, Rajivan; et al.
Abstract : Introduction: In spite of advances in understanding and technology, postoperative pain remains poorly treated for a significant number of patients. In colorectal surgery, the need for developing novel analgesics is especially important. Patients after bowel surgery are assessed for rapid return of bowel function and opioids worsen ileus, nausea and constipation. We describe a prospective, double-blind, parallel group, placebo-controlled randomised controlled trial testing the hypothesis that a novel analgesic drug, VVZ -149, is safe and effective in improving pain compared with providing opioid analgesia alone among adults undergoing laparoscopic colorectal surgery. Methods and analysis: Based on sample size calculations for primary outcome, we plan to enrol 120 participants. Adult patients without significant medical comorbidities or ongoing opioid use and who are undergoing laparoscopic colorectal surgery will be enrolled. Participants are randomly assigned to receive either VVZ-149 with intravenous (IV) hydromorphone patient-controlled analgesia (PCA) or the control intervention (IV PCA alone) in the postoperative period. The primary outcome is the Sum of Pain Intensity Difference over 8 hours (SPID-8 postdose). Participants receive VVZ-149 for 8 hours postoperatively to the primary study end point, after which they continue to be assessed for up to 24 hours. We measure opioid consumption, record pain intensity and pain relief, and evaluate the number of rescue doses and requests for opioid. To assess safety, we record sedation, nausea and vomiting, respiratory depression, laboratory tests and ECG readings after study drug administration. We evaluate for possible confounders of analgesic response, such as anxiety, depression and catastrophising behaviours. The study will also collect blood sample data and evaluate for pharmacokinetic and pharmacodynamic relationships. Ethics and dissemination: Ethical approval of the study protocol has been obtained from Institutional Review Boards at the participating institutions. Trial results will be disseminated through scientific conference presentations and by publication in scientific journals. Trial registration number: NCT02489526 ; pre-results.